Inflation and Economic Growth Link – Multi-Country Scenario - Ahmmed, Monir; Uddin, Md. Nezum; Rafiq, Md. Rafiqul Islam; Uddin, Mohammed Jashim (International Journal of Economics and Financial Issues, 2020)
This paper inspects the intercommunication between inflation and economic growth for ten (10) selected countries using annual data series collected from World Bank Development Indicator. GDP and CPI data are used in this regard. Series are found to be stationary at level 1. Residual and Johansen Cointegration tests confirm the long-run relationship between variables. Short-run dynamics are checked by the Error Correction Model. Desired negative signs are contained in the ECT for all sequences, and absolute values are less than 1. Except for the UK data, the inflation imbalance will be adjusted by economic growth for all countries and vice versa. The ECT of India is observed to be high-0,736 and-0862, suggesting that 73% and 86% of imbalances would converge in long-term equilibrium owing to shifts in inflation and economic growth, respectively. The sensitivity of inflation to growth and vice versa varies from country to country. The study also shows that the association between inflation and economic growth is favorable for some countries and the opposite for other countries. Such outcomes lead policymakers to enact policies to regulate the economy in the context of macroeconomic management. Keywords: Multi-countries, Consumer Price Index, Economic growth rate, Cointegration, Error Correction Model. JEL Classifications: E20, E31, E32, O5, O40, O47 DOI: https://doi.org/10.32479/ijefi.9942